The social image of families of children and youth in residential care: a characterization and comparison with mainstream families with different socioeconomic status - Patrício, J.; Lopes, D.; Garrido, M. V.; Calheiros, M. M. (Journal of Family Issues, 2019)
The literature suggests that families of children and youths in residential care are often associated with negative social images. These images may shape prejudiced attitudes and behavior toward them and, when shared by care professionals, compromise the effectiveness of family intervention and reintegration. This study explored these social images in a sample of 176 participants with and without professional contact with this population. Participants were asked to indicate five attributes describing families of children or youths living in residential care or in mainstream environments with low or medium socioeconomic status (SES). Results indicated that both families of children and youths in residential care and families of low SES were predominantly described with negative attributes. However, only the former were characterized by dysfunctional parenting-related attributes. Medium SES families were overall described with positive attributes. Furthermore, these social images were organized in different profiles. Implications for family intervention and reintegration are discussed.